Experimental study of droplet evaporation boiling curve using aluminium - Mardhiah Abdul Wahab (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This experiment is about study of the water droplet evaporation boling curve using aluminium. Boiling is the most familiar from of heat transfer. Boiling takes different forms, depending on the value of the temperature. There are four different boiling regimes was observed that is natural convection boiling, nucleate, transition boiling, and film boiling. The problem statement in the experimental study is to develop droplet evaporation boiling curve using aluminium.